Game Theory Based Security Approach in Wireless Sensor Network - Muruganandam, A; Anitha, R (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor networks have gone through a lot of changes in recent years. Secrecy in data transmission and network standby time are a major concern in communication. Currently, DSR algorithm is used for transmission of data between nodes. The algorithm determines the path for data to be transmitted to the destination node. Once the path is determined, all data are transmitted through the path. This method of data transmission drains the battery of the nodes quickly when the nodes are stationary. All the data are transmitted in a single stretch through the data path selected. When someone gains access to this path, all the data can be collected, and the entire network is compromised. A theory is implemented for eliminating this game. The data path is selected such that the battery level of all the nodes is effectively used. The data are spit and transmitted using more than one path for enhancing data security.